Application of a novel vegetation condition index using MODIS EVI for structuring crop index insurance under a smallholder system - Andualem Aklilu Tesfaye; Daniel Edward Osgood; Berhane Gessesse Aweke (Environmental and Sustainability Indicators)
Because of the ongoing pressure from climate change, there is a greater need for improved crop index insurance systems, and earth observation technology has made this possible. Accordingly, this study aims to develop a novel crop index insurance scheme using an innovative approach of developing a Vegetation Condition Index derived from Enhanced Vegetation Index (VCI-evi) that potentially addresses the limitations of existing products. This study is placed in a widely known drought-affected district of Ethiopia, the Amhara region. The study took advantage of a 16-day composite of MODIS EVI and a well-archived historical (2007–2022) in-situ data on drought prevalence, which is managed by the R4 crop insurance program, one of the well-established insurance schemes at a global scale. Across the study districts, using the VCI-evi variable, drought is predicted at a confidence interval greater than or equal to 99 %. The proposed approach is applied to establish index insurance parameters, notably, trigger and exit thresholds, as well as payout. Due to the wider prevalence of drought, which is strongly predicted and validated, across all the study villages in the years of 2015, 2016, 2018 and 2011, those years were identified as major drought years. Data on farmers’ bad years ranking was used to validate and revealed a higher level of agreement with model-predicted drought years. Therefore, the approach which is introduced in this study could be used to design an original index insurance scheme in several drought-prone systems offering increased reliability and enhanced scale-up.